Developing iSWITCHED (Implementing SWITCHing EDucational Intervention): A Co-Designed Intervention to Support Safer Antipsychotic Switching in Severe Mental Illness - Prachi Kaistha; Megan Beddow; Tom Kingstone; Ian Maidment; Saeed Farooq (BJPsych Open)
Aims: Individuals with severe mental illness (SMI) face two–three times higher-risk of early death; over 60% are deaths linked to preventable physical health issues. Commonly prescribed antipsychotics (APs) like olanzapine, quetiapine, and risperidone effectively manage mental health (MH) symptoms but carry serious cardiometabolic risks. Although lower-risk APs have been available for nearly a decade, most patients remain on higher-risk APs as switching to improve cardio-metabolic side-effects is rarely implemented due to clinician uncertainty and relapse concerns. We aimed to co-design an educational intervention to support clinicians in evidence-based AP switching, incorporating input from clinicians, patients and caregivers.